Self-oscillations of aircraft landing gear shock-strut at considerable non-linear friction - Шифрин, Б.М. (Proceedings of National Aviation University (archive), 2004)
The report considers self-oscillations at ε >1. The previous works were dedicated to the elastic frictional L.G. shock strut oscillations, the mathematical model of which is a non-linear differential equation with low ε parameter of its right-hand part.